Aurora A kinase and its substrate TACC3 are required for central spindle assembly. (26th July 2013) - Lioutas, Antonios; Vernos, Isabelle
Abstract : Cell division entails a marked reorganization of the microtubule network to form the spindle, a molecular machine that ensures accurate chromosome segregation to the daughter cells. Spindle organization is highly dynamic throughout mitosis and requires the activity of several kinases and complex regulatory mechanisms. Aurora A (AurA) kinase is essential for the assembly of the metaphase bipolar spindle and, thus, it has been difficult to address its function during the last phases of mitosis. Here, we examine the consequences of inhibiting AurA in cells undergoing anaphase, and show that AurA kinase activity is necessary for the assembly of a robust central spindle during anaphase. We also identify TACC3 as an AurA substrate essential in central spindle formation. Aurora A kinase and its substrate TACC3 are required for central spindle assembly: This study shows that Aurora A‐in addition to its role metaphase bipolar spindle assembly‐is required for the generation of a robust anaphase central spindle. Aurora A substrate TACC3 participates in this process.